Ghrelin Signalling on Food Reward: A Salient Link Between the Gut and the Mesolimbic System - Perello, M. (J Neuroendocrinol, 2015)
‘Hunger is the best spice’ is an old and wise saying that acknowledges the fact that almost any food tastes better when we are hungry. The neurobiological underpinnings of this lore include activation of the brain's reward system and the stimulation of this system by the hunger‐promoting hormone ghrelin. Ghrelin is produced largely from the stomach and levels are higher preprandially. The ghrelin receptor is expressed in many brain areas important for feeding control, including not only the hypothalamic nuclei involved in energy balance regulation, but also reward‐linked areas such as the ventral tegmental area. By targeting the mesoaccumbal dopamine neurones of the ventral tegmental area, ghrelin recruits pathways important for food reward‐related behaviours that show overlap with but are also distinct from those important for food intake. We review a variety of studies that support the notion that ghrelin signalling at the level of the mesolimbic system is one of the key molecular substrates that provides a physiological signal connecting gut and reward pathways.